GAMBARAN PENGETAHUAN BIDAN TENTANG SDIDTK (STIMULASI, DETEKSI, DAN INTERVENSI DINI TUMBUH KEMBANG) PADA BALITA USIA 2 TAHUN DI PUSKESMAS BATURADEN I DAN PUSKESMAS KALIBAGOR KABUPATEN BANYUMAS TAHUN 2014 - Etika Dewi Cahyaningrum; Atin Mawarni (Universitas Harapan Bangsa Purwokerto, 2015)
Background : Health development as part of efforts to develop human, amongothers, held through the efforts of the health of children, with stimulation,detection, and early intervention developmental done as early as possible.Approximately 16% of children under five years old (toddlers) Indonesiaexperienced neurodevelopmental disorders and brain from mild to severe, and 2out of 1,000 babies impaired motor development, hence the need to speeddiagnosis and therapy for the healing process. Coverage SDIDTK (Stimulation,Detection and Interverensi Growth) in Puskesmas Puskesmas KalibagorBaturaden 7.41% and 26.18%. Midwives spearhead SDIDTK activities should bewell trained and knowledgeable in the use and development of the body intervenetoddlers.Objective : The purpose of this study was to determine the description ofMidwives Knowledge About SDIDTK (stimulation, detection and earlyintervention developmental) in Toddlers Age 2 Years in health centers and healthcenters Baturaden I Kalibagor Banyumas 2014.Method : The research method using a type of research that is descriptivequantitative with cross sectional approach. This study uses primary data taken inAugust 2014 at the Health Center and Health Center Baturaden I KalibagorBanyumas. Sempel retrieval using the technique with the number of total sampleof 30 respondents.Result : The results of this study are most midwives in health centers andKalibagor Baturaden I have good knowledge of as many as 19 respondents(63.3%) and sufficient knowledge of 11 respondents (36.6%). Keyword : Knowledge, Midwife, SDIDTK